Interplay between charge density wave and superconducting phases in transition metal dichalcogenides and interfaces - Moura, Victor Nocrato (2023)
The competition between two different collective states and their interplay are standing questions in solid-state physics. The discovery of high-temperature superconductivity in materials brought a new spectrum of compounds that exhibit competition between superconductivity and another collective state, such as density waves (charge/spin density waves). In recent studies, transition-metal dichalcogenides (TMDs) show emergent superconductivity when doped. It was suggested the fluctuations of their charge density wave (CDW) order, in the form of discommensurations, are closely related to enhancing the superconductor’s critical temperature. With a novel technique based on scanning tunneling microscopy, it became possible to measure distinct amplitude and phase images of CDW with high spatial resolution. Such analysis in TMDs provides evidence that their charge density wave consists of three individual charge modulations. Phase images revealed topological defects and discommensurations in a nearly-commensurate state that was predicted by the McMillan theory. Recently, a Ginzburg-Landau-McMillan model was used to describe the CDW in TMDs, specifically in TiSe2. In this thesis, first, we theoretically examine the behavior of superconductivity at parallel interfaces with other dominant collective excitation, such as charge density waves or spin density waves. Due to their competitive coupling in a two-component Ginzburg-Landau model, suppression of the prevailing order parameter at the interfacial planes allows for nucleation of the (hidden) superconducting order parameter at those planes. Then, we investigate the role of the different parameters within the Ginzburg-Landau-McMillan theory on the phase distribution, discommensurations, and critical temperatures of CDW in 2D materials and how these parameters influence the superconductivity. We employ an imaginary time evolution method on the Ginzburg-Landau-McMillan equations to obtain first the CDW discommensuration distributions and then the superconductivity.